Organisasi Pengelola Zakat Komparasi Standar Akuntansi Organisasi Nirlaba Dan Standar Akuntansi - Efri, Supriyanti (UIN Sunan Kudus, 2018)
Institute of Accountants (IAI) issued Statement of Financial Accounting Standards (PSAK) One of the parameters of public tust in zakat management organization is financial reporting based on accounting and application of sharia principles in it. To this end, the Indonesian No. 109 on zakat accounting standards. Previously the zakat management organization still uses PSAK No. 45 on non-profit accounting. This study aims to provide an overview of accounting standards of nonprofit organizations and accounting standards of zakat management organizations in Indonesia as well as to make comparisons between the two. This study is a literature study. The results of this study indicate there are some differences between non-profit accounting standards with zakat accounting standards. In zakat management organizations there are elements of sharia and it is not found in non-profit organizations in general, there are components of different financial statements which in the organization of zakat management there are additional components, namely: reports on changes in management assets, and so on.